A method for preparing a multi-stage slow-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material
Through the multi-stage sustained release prefabricated block preparation method, the problems of low yield and uneven dispersion of TiB2 micro-nanoparticles in magnesium lithium-based composite materials were solved, and efficient enhancement of magnesium lithium-based composite materials was achieved, which significantly improved its strength. Modulus and elongation.
Patent Information
- Application Number
- CN202310097359.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-02-01
AI Technical Summary
In the stirred casting method, the yield of TiB2 micro-nanoparticles in the magnesium-lithium-based composite material is low, the micro-scale particles are prone to settle, and the nano-scale particles are prone to float, resulting in uneven dispersion of the reinforcement particles in the melt, affecting the composite Material properties.
Using the multi-stage sustained release prefabricated block preparation method, micron, submicron and nanoscale TiB2 particles were mixed with aluminum powder respectively, and then hot pressing and cold pressing were used to form external nano-scale, internal submicron and micro-scale particles. Multi-layer structure prefabricated blocks ensure uniform dispersion of particles of different sizes in the melt.
The uniform dispersion of TiB2 particles in the melt of magnesium lithium-based composite material is achieved, the yield of reinforcement particles is improved, the strength, modulus and elongation of the composite material is significantly improved, while maintaining the low density characteristics.
Smart Images

Figure CN116213714B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a prefabricated block for micro-nano particle reinforced magnesium-lithium based composite materials, and in particular to a method for preparing a multi-stage sustained-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite materials, belonging to the field of metal-based composite materials and their preparation. Background Art
[0002] Against the backdrop of global energy shortages and increasingly severe environmental problems, the transformation of industrial technology towards "low carbonization" and "lightweighting" is an inevitable trend. Therefore, in the fields of consumer electronics, aerospace, and military equipment, the development of structural materials with low density and high strength is a hot topic for researchers. As one of the lightest metal structural materials currently available, magnesium-lithium alloys have a density of less than 1.6 g / cm 3 On the premise of ultra-light characteristics, it also has high specific stiffness, specific strength, good elongation and machinability, and excellent electromagnetic shielding performance. However, magnesium-lithium alloys still have problems such as low absolute strength and stiffness, and serious aging softening, which limits their promotion and application in various fields. The traditional way to strengthen magnesium-lithium alloys is to improve the strength of the alloy by alloying and heat treatment. Tang Song et al. disclosed "A high-strength and high-thermal stability ultra-light magnesium-lithium alloy and its preparation method" (publication number CN114231809A), using Ag as an alloying element, while improving the strength and thermal stability of magnesium-lithium alloys. However, the elastic modulus of magnesium-lithium alloys is difficult to be effectively improved by alloying and heat treatment methods. The use of composite materials to introduce high modulus phases into magnesium-lithium alloys can effectively improve the problem of low elastic modulus of magnesium-lithium alloys.
[0003] At present, the commonly used high modulus reinforcements in metal matrix composites mainly include carbon nanotubes, oxide particles and ceramic particles. Due to the high activity of lithium, the use of carbon nanotubes will react with lithium, and the generated compounds will reduce the interface strength of the composite material. The elastic modulus of oxide particles such as Al2O3 is not high enough, and the elastic modulus of the composite material is not significantly improved. The use of TiB2 ceramic particles (elastic modulus of 550GPa) can effectively improve the elastic modulus of magnesium-lithium alloys.
[0004] Industrially, due to the low cost and achievable large-scale preparation, metal-based composite materials are mostly prepared using stirring casting. Using stirring casting to prepare magnesium-lithium-based composite materials, the main difficulty is how to improve the wettability of reinforcement particles in the metal melt, improve the yield of reinforcement particles and realize the controllable rate of reinforcement particle addition. Wu Guoqing et al. prepared YAl2 preforms by the prefabricated block preparation method of cold pressing-hot pressing-hot extrusion, and the yield of YAl2 particles reinforced Mg-Li-based composite materials obtained was significantly improved, and the strength was significantly improved ("A Mg-Li-based composite material and its preparation method" publication number CN104789841A). However, due to the preparation method restrictions of its prefabricated blocks, only reinforcement particles of the same scale can be used. When adding reinforcement particles of different micro-nano scales, micron-sized particles are easy to settle, and nano-sized particles are easy to float on the melt surface, and the dispersion behavior of reinforcement particles in the melt cannot be effectively controlled by graded control, resulting in low performance of composite materials. Therefore, it is necessary to develop new methods to achieve the preparation of multi-stage sustained-release prefabricated blocks of TiB2 micro-nanoparticle reinforced magnesium-lithium based composites. Summary of the invention
[0005] The purpose of the present invention is to propose a method for preparing a multi-stage slow-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium-based composite material, aiming at the low yield of reinforcement particles in the alloy melt, the easy sedimentation of micron-sized particles, the easy floating of nano-sized particles on the melt surface, and the serious agglomeration of reinforcement particles due to the uncontrollable speed of reinforcement particles entering the melt in the preparation process of stirring casting micro-nano particle reinforced magnesium-lithium-based composite material. The present invention uses micron, submicron and nanometer TiB2 particles to be ball-milled with micron aluminum powder respectively, and obtains multi-stage slow-release prefabricated blocks with different degrees of internal and external bonding by hot pressing and cold pressing. In the preparation process of stirring casting magnesium-lithium based composite materials, the multi-stage slow-release prefabricated block can realize the uniform dispersion of reinforcement particles of different sizes in the melt: the multi-stage slow-release prefabricated block is placed inside the melt of magnesium-lithium alloy, the outer layer of nano-TiB2 particles enters the melt first, followed by the submicron TiB2 particles dispersed into the melt, and the micron TiB2 particles with the fastest sedimentation rate enter the melt last, followed by casting and forming, which ensures the recovery rate of reinforcement particles and realizes the process of uniform dispersion of multi-scale reinforcement particles into the magnesium-lithium melt.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing a multi-stage slow-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material, comprising the following steps:
[0008] S1, taking TiB2 particles of different micro-nano sizes and mixing them with aluminum powder particles for ball milling, respectively, to obtain composite powders of micron-sized TiB2 particles and aluminum powder, composite powders of submicron-sized TiB2 particles and aluminum powder, and composite powders of nano-sized TiB2 particles and aluminum powder;
[0009] S2, hot pressing the micron-sized TiB2 particles and the aluminum powder composite powder to obtain a primary prefabricated block;
[0010] S3, wrapping the submicron TiB2 particles and aluminum powder composite powder outside the primary prefabricated block, and performing cold pressing treatment to obtain a secondary prefabricated block;
[0011] S4. Wrap the nano-sized TiB2 particles and aluminum powder composite powder outside the secondary prefabricated block, perform cold pressing again to obtain a multi-stage sustained-release prefabricated block, and finally wrap it with aluminum foil and store it in a vacuum.
[0012] Preferably, before step S1, the method further includes performing ultrasonic cleaning treatment on TiB2 particles and aluminum powder of different micro-nano sizes, and removing oil stains and impurities on the surface of the particles using anhydrous ethanol.
[0013] Preferably, the diameter ranges of TiB2 particles of different micro-nano sizes are: micron level: 1-20 μm, submicron level: 0.1-1 μm, nanometer level: 1-100 nm.
[0014] Preferably, the diameter of the aluminum powder particles ranges from 10 to 100 μm.
[0015] Preferably, in step S1, the rotation speed of the mixed ball mill is 150-400 rpm, the ball milling time is 4-24 hours, and the ball-to-material ratio is 4:1-20:1.
[0016] Preferably, in step S1, the mass ratio of particles in the mixed ball mill is: TiB2 particles: aluminum powder particles = 2:1 to 1:1. Using this mass ratio can reduce the aluminum content in the matrix alloy and ensure the low density characteristics of the composite material. Using a higher aluminum content will result in too high an aluminum content in the collective alloy, a decrease in elongation and an increase in density.
[0017] Preferably, the mold used for hot pressing to prepare the primary prefabricated block is a stainless steel cylindrical mold. The hot pressing temperature is 300-450°C, the pressure is 50-70MPa, and the heat preservation and pressure holding time is 20-30min.
[0018] Preferably, in step S3, the mold used for preparing the secondary prefabricated block by cold pressing is a stainless steel cylindrical mold. The cold pressing is performed at room temperature (15-30° C.), the pressure is 30-50 MPa, and the holding time is 15-30 min.
[0019] Preferably, in step S4, the mold used for preparing the multi-stage sustained-release prefabricated block by cold pressing is a stainless steel cylindrical mold. The cold pressing is performed at room temperature (15-30° C.), the pressure is 15-30 MPa, and the holding time is 15-30 min.
[0020] Preferably, the mass percentages of the composite powder of micron-sized TiB2 particles and aluminum powder, the composite powder of submicron-sized TiB2 particles and aluminum powder, and the composite powder of nano-sized TiB2 particles and aluminum powder in the multi-stage slow-release prefabricated block are respectively 20-40%, 40-70%, and 10-40%. Using this mass percentage range, the reinforcing effects of micron-sized, submicron-sized, and nano-sized reinforcements can be simultaneously utilized to enhance the toughness of the composite material. Composite materials prepared using prefabricated blocks with other mass percentages will have problems of poor reinforcement effect and uncoordinated strength and plasticity. More preferably, the mass percentage of the composite powder of nano-sized TiB2 particles and aluminum powder is 10-20%.
[0021] The present invention obtains a multi-stage slow-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite materials by mixing and ball-milling TiB2 particles of different micro-nano sizes with aluminum powder, and performing multi-stage hot pressing and cold pressing. The multi-stage slow-release prefabricated block overcomes the problems of low yield of general reinforcement particles when added to magnesium-lithium alloy melt, uncontrollable speed of micro-nano particles entering the melt, and easy agglomeration of reinforcement particles.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention uses multi-stage hot pressing and cold pressing to form the prefabricated block, so that the external nano-scale TiB2 reinforcement particles are weakly bound, while the internal micron-scale TiB2 particles are strongly bound. When dispersed in the melt, the external nano-particles enter the melt first, avoiding the floating phenomenon caused by adding from the melt surface, while the micron-particles that are easy to settle are dispersed in the final stage and then cast immediately. At this time, the micron-scale TiB2 has not yet settled in large quantities, so the reinforcement yield of the magnesium-lithium based composite material can be effectively improved.
[0024] 2. The present invention adopts the method of mixed ball milling, multi-stage hot pressing and cold pressing to make the prefabricated block have a multi-layer structure that is tight inside and loose outside, and realizes the orderly and controllable release of TiB2 of different micro-nano scales inside the melt, so that the reinforcement particles can fully and evenly wet the melt, and avoids the agglomeration problem when a large number of reinforcement particles enter the melt at the same time.
[0025] 3. The present invention uses TiB2 particles of different micro-nano sizes as reinforcements at the same time, which can achieve the synergistic reinforcement effect of particles of different sizes in the composite material, which can not only ensure the improvement of the strength and modulus of the composite material, but also maintain the elongation of the composite material to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0027] Figure 1 A schematic diagram of a multi-stage sustained-release prefabricated block of TiB2 micro-nano particles used for preparing a magnesium-lithium based composite material according to the present invention;
[0028] Figure 2 The metallographic diagram of the magnesium-lithium based composite material prepared by using the prefabricated block of the present invention. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0030] Example 1
[0031] This embodiment relates to a method for preparing a multi-stage sustained-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material. The diameters of TiB2 micro-nano particles used in the prefabricated blocks are: micron level: 20 μm, submicron level: 0.5 μm, nanometer level: 100 nm, and the diameter of the micron aluminum powder used is 100 μm.
[0032] The method for preparing the multi-stage slow-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material is as follows:
[0033] 1) Use ultrasonic cleaning equipment to ultrasonically treat micro-nano TiB2 particles of different sizes and micron aluminum powder in anhydrous ethanol to fully remove oil stains, impurities and oxides on the surface of the particles, and then filter and dry them.
[0034] 2) TiB2 particles and aluminum powder were mixed and ball-milled on a planetary ball mill to prepare a mixed powder, the mass ratio of the mixed powder was TiB2: aluminum powder = 2: 1, the ball milling speed was 400 rpm, the ball milling time was 4 hours, and the ball-to-material ratio was 10: 1. The mass percentages of the micron-sized TiB2 particles and aluminum powder composite powder, submicron-sized TiB2 particles and aluminum powder composite powder, and nano-sized TiB2 particles and aluminum powder composite powder (three types of composite ball-milled powders) used to prepare the multi-stage slow-release prefabricated blocks were: 20%, 50%, and 30%.
[0035] 3) hot pressing the composite powder of micron-sized (20 μm) TiB2 and aluminum powder after ball milling, with the hot pressing parameters of 450°C, 50 MPa, and heat preservation and pressure maintenance for 20 minutes, using a stainless steel cylindrical mold to obtain a primary prefabricated block;
[0036] 4) Wrap the submicron (0.5 μm) TiB2 and aluminum powder ball-milled composite powder outside the primary prefabricated block and perform cold pressing treatment at a cold pressing pressure of 50 MPa for 30 min using a stainless steel cylindrical mold to obtain a secondary prefabricated block;
[0037] 5) Wrap the composite powder of nanoscale (100 nm) TiB2 and aluminum powder after ball milling outside the secondary prefabricated block, and perform cold pressing again at a pressure of 15 MPa for 15 min. Use a stainless steel cylindrical mold to obtain a multi-stage slow-release prefabricated block for subsequent smelting and preparation of magnesium-lithium based composite materials. Figure 1 Schematic diagram of the multi-stage sustained-release prefabricated block of TiB2 micro-nano particles used in the preparation of magnesium-lithium based composite materials according to the present invention, as shown in FIG. Figure 1 The outermost layer shown is a composite powder of nano-scale TiB2 and aluminum powder, the middle layer is a composite powder of submicron TiB2 and aluminum powder, and the innermost layer is a composite powder of micron TiB2 and aluminum powder.
[0038] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of Example 1. The matrix alloy was selected from Mg-10Li-3Al alloy. The designed amount of TiB2 particles added was 8% by mass. The yield rate of TiB2 particles in the magnesium-lithium based composite material was 87%, the yield strength was 186 MPa, the tensile strength was 209 MPa, the elongation was 8.5%, the elastic modulus was 56.5 GPa, and the density was 1.57 g / cm 3 . Figure 2 The metallographic diagram of the magnesium-lithium based composite material prepared by using the prefabricated block of the present invention is as follows: Figure 2 It can be seen that the reinforcement particles of the composite material are evenly dispersed, well combined and have no obvious microstructure defects. The yield of the composite material is detected by inductively coupled plasma emission spectrometer and calculated. The test specimens and methods of tensile properties (yield strength, tensile strength and elongation) are based on the national standard GB / T228.1-2010, and the test specimens and methods of density and elastic modulus are based on the national standard GB / T22315-2008, the same below.
[0039] Example 2
[0040] This embodiment relates to a method for preparing a multi-stage sustained-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material. The diameters of TiB2 micro-nano particles used in the prefabricated block are: micron level: 1 μm, submicron level: 0.1 μm, nanometer level: 50 nm, and the diameter of the micron aluminum powder used is 80 μm.
[0041] The method for preparing the multi-stage slow-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material is as follows:
[0042] 1) Use ultrasonic cleaning equipment to ultrasonically treat micro-nano TiB2 particles of different sizes and micron aluminum powder in anhydrous ethanol to fully remove oil stains, impurities and oxides on the surface of the particles, and then filter and dry them.
[0043] 2) TiB2 particles and aluminum powder were mixed and ball-milled on a planetary ball mill to prepare a mixed powder, the mass ratio of the mixed powder was TiB2: aluminum powder = 1.5:1, the ball milling speed was 400 rpm, the ball milling time was 24 hours, and the ball-to-material ratio was 10: 1. The mass percentages of the three composite ball-milled powders of micron, submicron and nanometer TiB2 particles and aluminum powder used to prepare the multi-stage slow-release prefabricated blocks were: 20%, 40%, and 40%.
[0044] 3) hot pressing the composite powder of micron-sized (10 μm) TiB2 and aluminum powder after ball milling, with the hot pressing parameters of 350°C, 70 MPa, and heat preservation and pressure maintenance for 20 minutes, using a stainless steel cylindrical mold to obtain a primary prefabricated block;
[0045] 4) Wrap the submicron (0.1 μm) TiB2 and aluminum powder ball-milled composite powder outside the primary prefabricated block and perform cold pressing treatment at a cold pressing pressure of 35 MPa for 15 min using a stainless steel cylindrical mold to obtain a secondary prefabricated block;
[0046] 5) Wrap the composite powder of nanoscale (100nm) TiB2 and aluminum powder after ball milling outside the secondary prefabricated block, and cold press it again at a pressure of 30MPa for 15min. Use a stainless steel cylindrical mold to obtain a multi-stage slow-release prefabricated block for subsequent smelting and preparation of magnesium-lithium based composite materials.
[0047] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of Example 2. The matrix alloy was selected from Mg-11Li-2Zn alloy. The designed amount of TiB2 particles added was 8% by mass. The yield rate of TiB2 particles in the magnesium-lithium based composite material was 89%, the yield strength was 203 MPa, the tensile strength was 235 MPa, the elongation was 9.6%, the elastic modulus was 56.9 GPa, and the density was 1.58 g / cm 3 .
[0048] Example 3
[0049] This embodiment relates to a method for preparing a multi-stage sustained-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material. The diameters of TiB2 micro-nano particles used in the prefabricated block are: micron level: 10 μm, submicron level: 0.5 μm, nanometer level: 100 nm, and the diameter of the micron aluminum powder used is 100 μm.
[0050] The method for preparing the multi-stage slow-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material is as follows:
[0051] 1) Use ultrasonic cleaning equipment to ultrasonically treat micro-nano TiB2 particles of different sizes and micron aluminum powder in anhydrous ethanol to fully remove oil stains, impurities and oxides on the surface of the particles, and then filter and dry them.
[0052] 2) TiB2 particles and aluminum powder were mixed and ball-milled on a planetary ball mill to prepare a mixed powder, the mass ratio of the mixed powder was TiB2: aluminum powder = 1:1, the ball milling speed was 350 rpm, the ball milling time was 8 hours, and the ball-to-material ratio was 4: 1. The mass percentages of the three composite ball-milled powders of micron, submicron and nanometer TiB2 particles and aluminum powder used to prepare the multi-stage slow-release prefabricated blocks were: 40%, 50%, and 10%.
[0053] 3) hot pressing the composite powder of micron-sized (10 μm) TiB2 and aluminum powder after ball milling, with the hot pressing parameters of 450°C, 60 MPa, heat preservation and pressure holding for 30 minutes, using a stainless steel cylindrical mold to obtain a primary prefabricated block;
[0054] 4) Wrap the submicron (0.5 μm) TiB2 and aluminum powder ball-milled composite powder outside the primary prefabricated block and perform cold pressing treatment at a cold pressing pressure of 30 MPa for 30 min using a stainless steel cylindrical mold to obtain a secondary prefabricated block;
[0055] 5) Wrap the composite powder of nanoscale (100 nm) TiB2 and aluminum powder after ball milling outside the secondary prefabricated block, and perform cold pressing again at a pressure of 15 MPa for 15 min. Use a stainless steel cylindrical mold to obtain a multi-stage slow-release prefabricated block for subsequent smelting and preparation of magnesium-lithium based composite materials.
[0056] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of Example 3. The matrix alloy was selected from Mg-11Li-2Zn alloy. The designed amount of TiB2 particles added was 8% by mass. The yield rate of TiB2 particles in the magnesium-lithium based composite material was 79%, the yield strength was 185 MPa, the tensile strength was 201 MPa, the elongation was 4.6%, the elastic modulus was 55.8 GPa, and the density was 1.57 g / cm 3 .
[0057] Comparative Example 1
[0058] This comparative example relates to a method for preparing a multi-stage sustained-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material, the components of the prefabricated block are the same as those in Example 1. The method for preparing the prefabricated block is basically the same as that in Example 1, except that the first-stage prefabricated block is prepared by cold pressing instead of hot pressing, and the cold pressing parameters are the same as the parameters for preparing the second-stage prefabricated block.
[0059] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of comparative example 1. The matrix alloy was selected as Mg-11Li-2Zn alloy. The designed amount of TiB2 particles added was 8% by mass. The yield rate of TiB2 particles of the magnesium-lithium based composite material was 45%, the yield strength was 148MPa, the tensile strength was 156MPa, the elongation was 12%, the elastic modulus was 52.3GPa, and the density was 1.51g / cm 3 .
[0060] The prefabricated blocks prepared entirely by cold pressing had weak bonding of the internal micron TiB2 particles, resulting in significant sedimentation in the melt, resulting in a low yield of the reinforcement and poor reinforcement effect of the composite material.
[0061] Comparative Example 2
[0062] This comparative example relates to a method for preparing a multi-stage slow-release prefabricated block for TiB2 micro-nano particles reinforced magnesium-lithium based composite material, the components of the prefabricated block are the same as those in Example 2. The method for preparing the prefabricated block is basically the same as that in Example 2, except that the secondary and multi-stage slow-release prefabricated blocks are prepared by hot pressing instead of cold pressing, and the hot pressing parameters are the same as those for preparing the primary prefabricated block.
[0063] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of comparative example 2. The matrix alloy was selected as Mg-11Li-2Zn alloy. The designed amount of TiB2 particles added was 8% by mass. The yield rate of TiB2 particles of the magnesium-lithium based composite material was 15%, the yield strength was 145MPa, the tensile strength was 152MPa, the elongation was 20%, the elastic modulus was 51.1GPa, and the density was 1.49g / cm 3 .
[0064] The prefabricated blocks prepared entirely by hot pressing are very tightly bound as a whole, which makes it difficult to disperse in the melt, resulting in a very low yield of the reinforcement and poor reinforcement effect of the composite material.
[0065] Comparative Example 3
[0066] This comparative example relates to a method for preparing a multi-stage sustained-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material, the components of the prefabricated block are the same as those in Example 2. The preparation method of the prefabricated block is basically the same as that in Example 2, the only difference being that the pressing methods of the primary and secondary prefabricated blocks are interchanged, i.e., the primary one adopts cold pressing, the secondary one adopts hot pressing, and the pressing parameters remain unchanged.
[0067] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of comparative example 3. The matrix alloy was selected as Mg-11Li-2Zn alloy. The designed amount of TiB2 particles added was 8% by mass. The yield rate of TiB2 particles in the magnesium-lithium based composite material was 55%, the yield strength was 172MPa, the tensile strength was 196MPa, the elongation was 18%, the elastic modulus was 52.9GPa, and the density was 1.52g / cm 3 .
[0068] The prefabricated block is prepared by cold pressing in the first stage and hot pressing in the second stage. The external nanoparticles can be effectively added, but due to the strong bonding force of the second stage hot pressing, the yield of the micron TiB2 particles in the innermost part of the prefabricated block is low, and the reinforcement effect is not good.
[0069] Comparative Example 4
[0070] This comparative example relates to a method for preparing a multi-stage sustained-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material, and the components of the prefabricated block are the same as those in Example 3. The preparation method of the prefabricated block is basically the same as that in Example 3, except that the TiB2 and aluminum powder are not mixed and ball-milled, and the TiB2 powder and aluminum powder are directly mixed and uniformly and then hot-pressed and cold-pressed.
[0071] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of comparative example 4. The matrix alloy was selected as Mg-11Li-2Zn alloy. The designed amount of TiB2 particles added was 8% by mass. The yield rate of TiB2 particles of the magnesium-lithium based composite material was 35%, the yield strength was 125MPa, the tensile strength was 144MPa, the elongation was 2.3%, the elastic modulus was 52GPa, and the density was 1.51g / cm 3 .
[0072] In the prefabricated block obtained by directly mixing TiB2 powder and aluminum powder and then subjecting them to hot pressing / cold pressing treatment, the interface bonding between the reinforcement and aluminum powder is poor, which reduces the original improvement in the wettability of the TiB2 particles by ball milling, makes the reinforcement particles in the composite material more agglomerated, and significantly reduces the mechanical properties.
[0073] Comparative Example 5
[0074] This comparative example relates to a method for preparing a multi-stage sustained-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material, the components of the prefabricated block are the same as those in Example 2. The preparation method of the prefabricated block is basically the same as that in Example 2, except that the TiB2 particles and aluminum powder are not ultrasonically treated before ball milling.
[0075] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of comparative example 5. The matrix alloy was selected as Mg-11Li-2Zn alloy. The designed amount of TiB2 particles added was 8% by mass. The yield rate of TiB2 particles in the magnesium-lithium based composite material was 75%, the yield strength was 183 MPa, the tensile strength was 197 MPa, the elongation was 5.3%, the elastic modulus was 55.1 GPa, and the density was 1.56 g / cm 3 .
[0076] The TiB2 particles and aluminum powder were not ultrasonically treated before ball milling, and the impurities and oxides on the powder surface were not removed, which led to reduced interface bonding of the composite material and weakened the reinforcement effect of the reinforcement in the composite material.
[0077] Comparative Example 6
[0078] This comparative example relates to a method for preparing a multi-stage slow-release prefabricated block for TiB2 micro-nano particle reinforced magnesium-lithium based composite material, the components of the prefabricated block are the same as those in Example 2. The preparation method of the prefabricated block is basically the same as that in Example 2, except that the hot pressing temperature is adjusted to 600°C.
[0079] The magnesium-lithium based composite material was prepared by using the multi-stage slow-release prefabricated block of comparative example 6. The matrix alloy was selected from Mg-11Li-2Zn alloy. The TiB2 particle yield of the magnesium-lithium based composite material was 60%, the yield strength was 164MPa, the tensile strength was 188MPa, the elongation was 13.3%, the elastic modulus was 53.2GPa, and the density was 1.53g / cm 3 .
[0080] Due to the high hot pressing temperature, the aluminum powder in the primary prefabricated block was oxidized, resulting in a low yield of the reinforcement.
[0081] The present invention has many specific application paths, and the above is only a preferred embodiment of the present invention. It should be pointed out that the above embodiments are only used to illustrate the present invention, and are not used to limit the protection scope of the present invention. For those of ordinary skill in the art, several improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a multi-stage slow-release prefabricated block for TiB2 micro-nano particles reinforced magnesium-lithium based composite material, characterized in that: The method comprises the following steps: S1, taking TiB2 particles of different micro-nano sizes and mixing them with aluminum powder particles for ball milling, respectively, to obtain composite powders of micron-sized TiB2 particles and aluminum powder, composite powders of submicron-sized TiB2 particles and aluminum powder, and composite powders of nano-sized TiB2 particles and aluminum powder; S2, hot pressing the micron-sized TiB2 particles and the aluminum powder composite powder to obtain a primary prefabricated block; S3, wrapping the submicron TiB2 particles and aluminum powder composite powder outside the primary prefabricated block, and performing cold pressing treatment to obtain a secondary prefabricated block; S4, wrapping the nano-sized TiB2 particles and aluminum powder composite powder outside the secondary prefabricated block, cold pressing again to obtain a multi-stage sustained-release prefabricated block, and finally wrapping it with aluminum foil and vacuuming it for storage; During the preparation process of the magnesium-lithium based composite material by stirring casting, a multi-stage slow-release prefabricated block is placed inside the melt of the magnesium-lithium alloy.
2. The preparation method according to claim 1, characterized in that: Before step S1, the method also includes performing ultrasonic cleaning treatment on TiB2 particles and aluminum powder particles of different micro-nano sizes to remove oil stains and impurities on the surface of the particles.
3. The preparation method according to claim 1, characterized in that: The diameter ranges of TiB2 particles of different micro-nano scales are: micron level: 1-20 μm, submicron level: 0.1-1 μm, nanometer level: 1-100 nm; the diameter range of aluminum powder particles is: 10-100 μm.
4. The preparation method according to claim 1, characterized in that: In step S1, the rotation speed of the mixed ball mill is 150-400 rpm, the ball milling time is 4-24 hours, and the ball-to-material ratio is 4:1-20:
1.
5. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of particles in the mixed ball mill is: TiB2 particles: aluminum powder particles = 2:1 to 1:
1.
6. The preparation method according to claim 1, characterized in that: In step S2, the hot pressing temperature of the hot pressing treatment is 300-450°C, the pressure is 50-70MPa, and the heat preservation and pressure holding time is 20-30min.
7. The preparation method according to claim 1, characterized in that: The mold used for hot pressing to prepare the first-level prefabricated block is a stainless steel cylindrical mold; the mold used for cold pressing to prepare the second-level prefabricated block is a stainless steel cylindrical mold; the mold used for cold pressing to prepare the multi-stage sustained-release prefabricated block is a stainless steel cylindrical mold.
8. The preparation method according to claim 1, characterized in that: In step S3, the cold pressing treatment is carried out at 15-30°C, the pressure is 30-50 MPa, and the holding time is 15-30 min.
9. The preparation method according to claim 1, characterized in that: In step S4, the cold pressing treatment is carried out at 15-30°C, the pressure is 15-30 MPa, and the pressure holding time is 15-30 min.
10. The preparation method according to claim 1, characterized in that: The mass percentages of the composite powder of micron-sized TiB2 particles and aluminum powder, the composite powder of submicron-sized TiB2 particles and aluminum powder, and the composite powder of nano-sized TiB2 particles and aluminum powder in the multi-stage slow-release prefabricated block are 20-40%, 40-70%, and 10-40% respectively.
Citation Information
Patent Citations
Mg-Li composite material and preparation method thereof
CN104789841A
High-strength and high-thermal-stability ultralight magnesium-lithium alloy and preparation method thereof
CN114231809A
Shaped article and composite material and method for producing same
CA1197269A
Preparation method of micro-nano-scale reinforcement hybrid-reinforced magnesium-lithium-based composite material
CN111304505A